Certificate sharing system for secure certificate distribution in mobile environment. (February 2016) - Kim, Sundeuk; Oh, Hyun-Taek; Kim, Young-Gab
Highlights: We can share mobile certificates securely without modification of X.509 certificate. The certificate sharing system is implemented on a virtual private network. The certificate sharing system provides strong data security on physical devices. The certificate sharing system significantly improves convenience for users. The certificate sharing system provides a flexible and extensible system. Abstract: As mobile and Internet technologies evolve, mobile services (e.g., Internet banking, social commerce) continuously expand and diversify. In order to use these mobile services, it is essential that security services, especially distribution certificates (e.g., bank certificates), relevant to mobile devices be provided. Some approaches to providing distribution certificates between a user's mobile device and a personal computer (PC) have been proposed. However, the existing approaches do not guarantee that the certificate in the mobile devices same with the issued one from the PC, causing constraints on mobile services such as mobile phone banking and mobile commerce (M-commerce). In this paper, we propose a novel approach that shares certificates securely without modification of the existing standard certificate format between a smartphone and a PC. We also implemented the certificate sharing system (CSS) in a virtual private network (VPN). The CSS provides strong end-to-end data security for the certificate with a key size of 192-bits which is able to guarantee an expiration date of three years. It also provides strong data security on physical devices with the use of device ID. The certificate that is shared between devices is available only through the CSS's authorization process. In addition, the CSS provides a flexible and extensible system for sharing certificates in enterprise environments. The CSS module of a PC was implemented by way of a standard web language, and the CSS module of a smartphone was developed with the assistance of mobile applications with a small size of 1210KB.